MATHEMATICAL MODELS FOR ESTIMATING METHANE PRODUCTION IN COVERED LAGOON BIODIGESTERS TREATING PIG MANURE - Lopes,Juciara O. (2021)
ABSTRACT Covered lagoon biodigesters (CLB) have been widespread in Brazil in the treatment of pig manure. However, the quantification of biogas production in CLB using mathematical models is still limited and scarce. This study aimed to evaluate and compare six mathematical models—Chen-Hashimoto (Chen, 1983), CETESB (2006), COD Conversion (Chernicharo, 2016), IPCC (2006), Deng (Deng et al., 2014), and modified Stover-Kincannon (Yu et al., 1998)—usually used to estimate methane (CH 4 ), and propose improvements to the models, if necessary. The results were compared with the monitored production (P actual ) in a farm with CLB using the t-test (α = 5%). The Chen-Hashimoto, IPCC, Deng, and modified Stover-Kincannon models showed no statistical difference compared to P actual (405.0 m 3 CH 4 d −1 ), whereas the CETESB and COD Conversion models presented no statistical difference after the proposed improvements. All models can be considered reliable for estimating volumetric methane production after the adaptations, being relevant tools for diagnosis and decision-making regarding the energy recovery of biogas with CLB operation in pig farms.